THE EFFECT OF TRUST AND BRAND IMAGE ON PURCHASE DECISION (TOYOTA CAR SURVEY IN JAKARTA REGION) - Wibowo, Setyo Ferry; Sari, Elsyana Purnama; Saidani, Basrah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purpose of this research is to know: 1) influence of confidence to Toyota Agya car purchase decision in Jakarta area, and 2) influence of brand image to Toyota Agya car purchase decision in Jakarta area. The object of this research is 200 respondents of Toyota Agya car users in Jakarta area. Methods of data collection using survey method. Data analysis using SPSS 22. Descriptive test results explain that there is still a lack of trust and brand image in Toyota Agya car in the Jakarta area causing the lack of consumer response to make purchasing decisions. The result of hypothesis testing shows: 1) existence of positive and significant influence of trust toward purchasing decision, 2) existence of positive and significant influence from brand image to purchasing decision.